MODEL PEMBELAJARAN PENDIDIKAN KARAKTER DENGAN PENDEKATAN MULTIKULTURAL DALAM PENDIDIKAN KEWARGANEGARAAN DI PERGURUAN TINGGI - Al Atok, A. Rosyid; Hakim, Suparlan Al; Untari, Sri; M.Si, Margono (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstract: This research aims to develop a learning model character education with a multiculturalapproach used in Civic Education. The resulting learning model is poured in the form of modules andvisualized in the form of instructional videos. Framework of a prototype model of learning by takinginto account the competence of the subjects that must be owned by the students, faculty competencein multicultural approach, the cultural background of students, and the characteristics oflearning the nuances of multicultural material. Strategies that can be used, among others: strategiesand learning activities are combined with the concept attainment strategy, the strategy value analysis,and strategies of social analysis. Drafting of the learning can be done through five main stages,namely content analysis, the analysis of cultural background, mapping materials, organizing materials,and then poured in Civic Education learning format. In the implementation of character educationlearning model with a multicultural approach can be done through the following phases: ExplorationStudies, Presentations, Peer Group Analysis, Expert Opinion, and Reflections and Recommendations.Keywords: character education, multicultural, and civic education